2021
DOI: 10.1038/s41598-021-84711-x
|View full text |Cite
|
Sign up to set email alerts
|

An association between body image dissatisfaction and digit ratio among Chinese children and adolescents

Abstract: Body image dissatisfaction (BID) is a negative evaluation of personal physical characteristics, including dissatisfaction with body shape, gender, sexual organs, appearance and so forth, and it plays an important role in growth and development. The second-to-fourth digit ratio (2D:4D) is recognized as a putative indicator of intra-uterine testosterone to estrogen ratio exposure, and it has been observed that higher levels of fetal testosterone exposure are associated with a lower 2D:4D. The present paper contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
(34 reference statements)
1
3
1
Order By: Relevance
“…For example, sex differences in 2D:4D tend to be larger from hand photocopy assessments than they are from direct caliper measurements (Hönekopp & Watson, 2010). The magnitude of 2D:4D sex differences in our study is comparable to that in other studies that used direct caliper measurements (Austin et al, 2002;Barrett et al, 2021;Liu et al, 2012;Manning et al, 2009;Portnoy et al, 2015;Yuan et al, 2021) but smaller than that from studies that used hand photocopies (Berenbaum et al, 2009;Knickmeyer et al, 2011;Lutchmaya et al, 2004;Manning et al, 2000Manning et al, , 2004Millet & Dewitte, 2006;Putz et al, 2004;Wong & Hines, 2016). Few studies of 2D:4D and behavior have used direct caliper measurements, and among those that did, associations were not consistently found in both sexes, both hands, or in the expected directions, similar to our results (Austin et al, 2002;Barrett et al, 2021;Liu et al, 2012;Portnoy et al, 2015;Stevenson et al, 2007).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…For example, sex differences in 2D:4D tend to be larger from hand photocopy assessments than they are from direct caliper measurements (Hönekopp & Watson, 2010). The magnitude of 2D:4D sex differences in our study is comparable to that in other studies that used direct caliper measurements (Austin et al, 2002;Barrett et al, 2021;Liu et al, 2012;Manning et al, 2009;Portnoy et al, 2015;Yuan et al, 2021) but smaller than that from studies that used hand photocopies (Berenbaum et al, 2009;Knickmeyer et al, 2011;Lutchmaya et al, 2004;Manning et al, 2000Manning et al, , 2004Millet & Dewitte, 2006;Putz et al, 2004;Wong & Hines, 2016). Few studies of 2D:4D and behavior have used direct caliper measurements, and among those that did, associations were not consistently found in both sexes, both hands, or in the expected directions, similar to our results (Austin et al, 2002;Barrett et al, 2021;Liu et al, 2012;Portnoy et al, 2015;Stevenson et al, 2007).…”
Section: Discussionsupporting
confidence: 76%
“…The measurements had high ICCs, indicating adequate reliability. Additionally, there was indirect evidence of internal validity, since the 2D:4D sex differences were similar to those in previous studies that also utilized caliper measurements (Austin et al, 2002;Liu et al, 2012;Manning et al, 2009;Yuan et al, 2021). Third, we employed an outcome assessment instrument, the YSR questionnaire, that has been validated in populations similar to ours (Ivanova et al, 2007).…”
Section: Discussionmentioning
confidence: 61%
“…The results of this study showed that there was no significant difference in BSQS between boys and girls, however, the BSQS in boys with stage III was lower than that in boys with stage I. Our previous studies based on the same participants showed that there were no significant difference in body shape dissatisfaction score between girls and boys, were significant differences in gender dissatisfaction score, sexual organ dissatisfaction score in different puberty stages, 13 which may be because of the different scales (Teenage body image annoyance questionnaire (TBIAQ) and Body Shape Questionnaire (BSQ)) used for body image dissatisfaction. This is consistent with other previous findings that body image dissatisfaction tends to decline with advancing puberty in boys but not in girls.…”
Section: Discussioncontrasting
confidence: 47%
“…This study excluded participants with any primary or further endocrine condition, to prevent any potential interference with expression of digit ratios, as a result of underlying pathology. 49 However, in a pediatric population it is possible that conditions such as these may not have yet been diagnosed but could impact 2D:4D ratio measurements. Furthermore, there is a wide variation in age range, with our participants ranging from 2 to 16 years old.…”
Section: Limitationsmentioning
confidence: 99%